Between Dugin’s Eurasianism and Mahan’s Sea Power Concept: Russia’s Geopolitical Discourse within Foucault’s ‘Discursive Tree’ before and After the Incorporation of the Crimea - Cheriet, Taha (My University, 2016)
The fall of 2013 could be characterized as a crossroad in the geopolitics of Eastern Europe, namely Ukraine. Two rivalry geopolitical projects have been developing throughout the post-Cold War years, and it seems that they reached a collision point in Ukraine; a country whose authorities have been for long switching sides between the European Union and the Russian Federation in their foreign policy commitments. The refusal/postponing to sign the Association Agreement with Brussels, an expected event by a large category of the Ukrainian society, by Yanukovich’s government led to the outset of the latter; and brought a pro-Western, anti-Russian government in Kyiv. It seems that Ukraine, after those events, has embarked definitively on the path of integration into the West (European Union and possibly NATO). The Russian Federation, who has been throughout Putin’s years engaged into the re-integration of post-Soviet space, reacted to these developments in an assertive manner by violating borders, agreements and the territorial integrity of Ukraine. Thus, the incorporation of the Crimea into the Russian Federation is the first in its kind in the post-Soviet space, despite the existence of various other conflicts that broke out in the region after the Soviet Union broke up. I will investigate in this thesis the nature of what will be labelled, in this work, the Crimean issue. I argue that the incorporation of the Crimean peninsula into the Russian Federation marks a new era in Russian geopolitical thinking that shapes, to a far extent, Russian foreign policy. Discourse analysis will be the methodological basis for this study, with a special focus on Michel Foucault’s Archaeology of Knowledge. The innovation that this research brings is the fact that it discusses Russian geopolitical discourse within the scope of Foucault’s ‘discursive tree’, with a reference to the Crimean issue. A wide range of primary sources will be consulted in this study such as presidential addresses to the Federal Assembly (2000-2014), Foreign Policy Concepts of the Russian Federation (2000, 2008), Russian maritime doctrines, as wells as Dugin’s Osnovy Geopolitiki (Foundations of Geopolitics), Mahan’s (The Influence of Sea Power Upon History, 1660–1783) and other Eurasianism related literature.